Efficacy of Soya Protein Concentrates on the Performance and Immunity of Broiler Chickens - Zakaria, Hana A. H.; Ata, Murad R. (Frontiers in Veterinary Science, 2020)
A study was conducted to determine the effect of enzymatic treated soyaprotein concentrates (SPCE) on the productive performance and immunity of Ross 308 broiler chickens. A total of 800 chicks were randomly assigned to four dietary treatments (200 bird each), with four replicates per treatment (50 chicks / replicate). Diets were control diet without supplement (T0) or supplemented with T1 (140), T2 (160), and T3 (180) g/ bird of 5% SPCE, which replaced SBM in the basal starter diet at a rate of 5% (W/W). Each bird received a total of 300g of the starter diet during the first 12 days of rearing, and then was fed ad-libitum grower and finisher diets without SPCE inclusion for 35 d. On day 35, 2 birds / replicate were randomly selected and slaughtered for carcass evaluation. Results showed that T180 had the lowest body weight (P<0.05). FCR was significant (P<0.05) with treatments. T160, T180 showed the lowest mortality rate (P<0.05) on the 4th week. T160 had significant dressing %. Carcass characteristics were not affected by the treatments. Newcastle disease blood titers showed significant higher protection provided for T180 and T160 birds on d 20. Avian Influenza blood titers gave best results with T180 at d 30 while Infectious Bursal Disease and Infectious Bronchitis blood titers were not affected by changing dietary levels with SPCE. In conclusion, results indicated that supplementing enzymatic treated soya protein concentrates to broiler chickens had some effects on performance and enhanced the immunity against Newcastle and Avian influenza diseases.